KISAH NUH A.S DALAM PERSPEKTIF AL-QUR'AN - Muhammad Thaib Muhammad (Jurnal Ilmiah Al-Mu'ashirah: Media Kajian Al-Qur'an dan Al-Hadits Multi Perspektif, 2017)
Noah a.s is the Apostle who was first sent by Allah SWT to his people who have deviated from the religion of nature (Islam). He conveyed his da'wah to his people for 950 years, in conveying da'wah a very tough challenge, because they scolded, denied, caught and beat him until Noah a.s helpless then throw him in the street. But Allah Almighty returns strength to him. Thus with his faith and passionate spirit, he returns to his task of preaching back and giving advice and telling them to abandon idolatry, by returning to worship Allah Almighty who can bring benefits and can distress kemudharatan. But they still reject it and deny it, insult and revile it. Thus he surrendered all to Allah (swt) by praying to Him to destroy them so that there would be a generation who believed and obeyed His commands. Then Allah SWT told Noah a.s to make a ship (the ark) as a savior himself with those who believe. After the boat is finished, God radiates water from all corners of the earth, bringing in a powerful cyclone and bringing down rain from the sky for 40 days and 40 nights. Thus the entire surface of the earth is flooded. All the inhabitants of the earth are destroyed, the only survivors Noah a.s and those who believe with him in the ship. After the great flood ended Noah a.s with his adherents landed on Mount Juudi Mousul Iraq. They descend from the ship on the day of 'Ashura or ten Muharram. Then Noah a.s fasted on that day as a sign of his gratitude for his salvation from the great disaster. Then he lived after the cyclone for 350 years. According to the story in the Torah that the age of Noah a.s reached 1350 years. Meanwhile, according to the Qur'an only describes his da'wah with his people for 950 years. As for his definite age God is surely the All-Knowing God. When he died he was buried near the Grand Mosque of Makkah.